A Population-Based Study of Care at the End of Life Among People With HIV in Ontario From 2010 to 2013. (1st May 2017) - Kendall, Claire E.; Chalifoux, Mathieu; Manuel, Doug; Reinhard, Robert; Robinson, Gregory; Bacon, Jean; Rourke, Sean B.; Rosenes, Ron; Tanuseputro, Peter
Abstract : Background: Aging and increasing comorbidity is changing the end-of-life experience of people living with HIV (PLHIV) in the developed world. We quantified, at a population level, the receipt of health care services and associated costs across a comprehensive set of sectors among decedents with and without HIV. Methods: We conducted a retrospective population-level observational study of all decedents in Ontario and their receipt of health care services, captured through linked health administrative databases, between April 1, 2010 and March 31, 2013. We identified PLHIV using a validated algorithm. We described the characteristics of PLHIV and their receipt of health care services and associated costs by health care sector in the last year of life. Results: We observed 264, 754 eligible deaths, 570 of whom had HIV. PLHIV were significantly younger than those without HIV (mean age of death 56.1 years vs. 76.6 years, [ P < 0.01]). PLHIV spent a mean of 20.0 days in an acute care hospital in the last 90 days of life compared with 12.1 days for decedents without HIV ( P < 0.01); after adjustment, HIV was associated with 4.5 more acute care days ( P < 0.01). Mean cost of care in the last year was significantly higher among PLHIV ($80, 885.62 vs. $53, 869.77), mostly attributable to acute care costs. Interpretation: PLHIV in Ontario are dying younger, spending more time and dying more often in hospital, and incur significantly increased costs before death. Greater involvement of community-based palliative care may improve the dying experience for this complex population. Abstract : Supplemental Digital Content is Available in the Text.